2021
DOI: 10.1021/acssuschemeng.0c08058
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Permeability Influencing the Performance of Free CH4 and Free CO2 during the Process of CO2 Sequestration and Enhanced Gas Recovery (CS-EGR) from Shale

Abstract: To explore how anisotropic permeability affects the performance of free gases (CO 2 and CH 4 ) during the process of sequestrate CO 2 and enhance gas recovery (CS-EGR) in shale reservoirs, this work develops an integrated thermo-hydromechanical (THM) coupling model, where the anisotropic parameter k (k = k h /k v ) is embedded, where k v and k h represent the permeability in the vertical and horizontal directions, respectively. Results indicate that anisotropic permeability has a significant influence on the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Anisotropy can trigger the existence of groundwater whirls [19,20] that may have a large influence on reactive transport and dilution processes. Anisotropy can impact the efficiency of greenhouse gases (such as CO 2 ), sequestration in deep geological formations [21], and heat extraction by geothermal boreholes [22].…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropy can trigger the existence of groundwater whirls [19,20] that may have a large influence on reactive transport and dilution processes. Anisotropy can impact the efficiency of greenhouse gases (such as CO 2 ), sequestration in deep geological formations [21], and heat extraction by geothermal boreholes [22].…”
Section: Introductionmentioning
confidence: 99%
“…143 Zhao et al established a coupled thermo-hydro-mechanical (THM) model to investigate the effect of permeability on gases in fractured shale reservoirs, and confirmed that matrix rocks and natural fractures are highly dependent on stress. 144 3.2.2. Pore Network Modeling.…”
Section: Diffusion and Flowmentioning
confidence: 99%
“…Wei et al established shale double effective stress for organic matter, matrix pores, natural fractures, and discrete artificial fractures, and the influence of rock deformation on shale gas flow between matrix and fracture was analyzed . Zhao et al established a coupled thermo-hydro-mechanical (THM) model to investigate the effect of permeability on gases in fractured shale reservoirs, and confirmed that matrix rocks and natural fractures are highly dependent on stress …”
Section: Multiscale Flow Simulationmentioning
confidence: 99%
“…At present, the type of gas storage in China is vertical, that is, the vertical span of the solution chamber is greater than the horizontal span [15,16]. Compared with the salt mounds in other countries which are particularly thick, the salt rock deposits in China are typically thin in single layers and many in interlayers [17] because in the underground storage of salt rock, the wall of the cavity is often under alternating and cyclic load; that is, the internal pressure of the reservoir uctuates circularly between the minimum and maximum, and the fatigue microcracks can occur in the surrounding rock of cavities [18][19][20]. After that, the micro fractures gradually expanded, evolved, and penetrated with time, and macro fractures are formed nally.…”
Section: Introductionmentioning
confidence: 99%